Utilization and Suitability of The Information Technology Task Against The Performance of Semarang Tax Office - Sayudha, Vincent Bastian Tertio (EAJ (Economic and Accounting Journal), 2020)
Information technology has become part of human life to work, even it is very important in business organizations to be important in the timeliness and correctness of the provision of information technology at work. The.purpose.of.this study.is.to.analyze.and describe influence information technology and technological tasks individual performance. The population in this study were employees of the Candisari Pratama Tax Service Office, the South Semarang Pratama Tax Service Office, the East Semarang Pratama Tax Service Office. The sampling used in this study used a purposive sampling method and obtained 100 tax employee respondents. The analysis technique used in this study is multiple regression analysis with the application of IBM SPSS 23. The results of this study indicate the use of information technology and the suitability of the information technology task are significantly related to individual performance. The advice given related to this research is that the pratama tax office needs to help improve information technology by adding supporting facilities provided by users and increasing the level of conformity of information technology tasks in compiling tax revenue based on resources that can help individuals with the maximum number of employees.